2020
DOI: 10.3389/fpsyg.2020.01355
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Psychometric Properties of the Body Perception Questionnaire–Short Form (BPQ-SF) Among Chinese College Students

Abstract: Objective: Body perception, including body awareness and reactivity, is featured in a range of mental health conditions. However, research on Chinese questionnaires assessing body perception has been surprisingly absent. The present study aimed to investigate the factor structure and psychometric properties of the Body Perception Questionnaire-Short Form (BPQ-SF) among Chinese. Methods: the current sample included 688 Chinese college students. Self-report scales were used to measure body perception, somatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…The aims of the present study were to adapt the BPQ into Italian language, to assess its psychometric characteristics in a sample of Italian subjects, and examine the associations between the subscales of BPQ and the sample characteristics. The confirmatory factor analysis showed comparable results to the English, Spanish, and Chinese versions previously described in the literature [ 1 , 19 ], with subscales reflecting body awareness, supradiaphragmatic autonomic reactivity, and subdiaphragmatic autonomic reactivity. All subscales also demonstrated strong internal consistency.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The aims of the present study were to adapt the BPQ into Italian language, to assess its psychometric characteristics in a sample of Italian subjects, and examine the associations between the subscales of BPQ and the sample characteristics. The confirmatory factor analysis showed comparable results to the English, Spanish, and Chinese versions previously described in the literature [ 1 , 19 ], with subscales reflecting body awareness, supradiaphragmatic autonomic reactivity, and subdiaphragmatic autonomic reactivity. All subscales also demonstrated strong internal consistency.…”
Section: Discussionsupporting
confidence: 75%
“…The Body Perception Questionnaire Short Form (BPQ-SF) is a self-report measure of the body awareness and experiences of autonomic reactivity [ 1 , 17 ]. It has demonstrated strong psychometric properties and a consistent factor structure across multiple languages [ 1 , 19 ]. It is composed of two domains: body awareness (26 items) and autonomic nervous system reactivity (ANSR; 20 items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [ 73 ] for the Chinese validation of BPQ-SF. The BOA factor, consisting of items related to the upper parts of the body (e.g., “watering or tearing of my eyes”) or to the whole body (e.g., “goose-bumps”) may reflect the convergence of cranial and spinal pathways integration in the brainstem, while the SUP factor may reflect the function exerted by VVC whose fibers originate in the NA in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is closely related to somatic symptoms such as impaired sleep, pain, and different somatic concerns, which can also be seen as an impairing factor regarding depressive symptoms [55]. Previous studies found a positive relation between somatic symptoms, depression, and the BPQ [56,57], indicating that the BPQ takes somatic aspects into account. Therefore, using the BPQ seems to be beneficial in studies focussing on depression.…”
Section: Discussionmentioning
confidence: 99%